Vestiges of old Madras, 1640-1800 - Love, Henry Davison, 1852- (London : Published for the Govt. of India, 1913)
History of Madras, India.
"Traced from the East India Company's records preserved at Fort St. George and the India Office, and from other sources."
Includes index.
Microfilm.
Keywords: Chennai (India) -- History